DIAGNOSTICS AND LONG-TERM OUTCOMES AFTER SURGICAL TREATMENT OF EPILEPSY IN CHILDREN WITH STRUCTURAL BRAIN CHANGES - E. A. Asatryan; K. B. Abramov; M. R. Mamatkhanov; K. E. Lebedev; A. Y. Efimtsev; Yu. M. Zabrodskaya; K. I. Sebelev; D. V. Ryzhkova; G. E. Trufanov; W. А. Khachatryan (Эпилепсия и пароксизмальные состояния)
Objective. To identify predictive factors of favourable outcomes in children with drug resistant epilepsy (DRE) associated with structural brain changes,  who received surgical treatment.  Methods. We performed  a retrospective  analysis of surgical treatment in 239 children with drug resistant epilepsy treated at the Pediatric Neurosurgery Department of the A. L. Polenov Russian Neurosurgical Institute from 2004 to 2014. The age of the patients varied between  2 and 18 years. The follow-up time ranged from 1 year to 10 years (on average 4.3 years). Results. According to magnetic resonance imaging (MRI), 223 (93.3%) patients had different structural brain changes. Among the patients, 47 (21.1%) had cerebral cicatrix, gliosis, cysts  and atrophic changes, 33 (14.8%) had malformations of the cortical development, 43 (19.3%) had benign brain tumors,  47 (21.1%)  had vascular malformations,  21 (9.4%)  had arachnoid cysts,  12 (5.4%)  had hippocampal sclerosis,  11  (4.9%)  had  phacomatosis, 5  (2.2%)  had  Rasmussen’s encephalitis,  and  4  (1.8%)  had  hypothalamic hamartoma.  Positron  emission  tomography  revealed the  areas of gray matter  hypometabolism in the  brain, which correspond to the areas of a metabolic deficiency around the epileptic focus. Favorable long-term outcomes of epilepsy surgery (class I according to Engel scale) were registered in 67.6% of the cases.  The most  favorable results (class I according to Engel scale) were achieved after lesionectomy (81.9%), temporal resections (78.4%), and hemispherectomy (72.7%).Conclusions. The most important predictive factors of favorable outcomes after epilepsy surgery are as follows: detection of epileptogenic morphological changes of the brain, completeness of resection of an epileptic and epileptogenic areas, and absense  of seizures in the early postoperative period.